Vitamin D receptor gene polymorphisms in ocular surface squamous cell neoplasms. Issue 5 (September 2020) - Ismayilova, Nergiz; Palamar, Melis; Onay, Huseyin; Ceylan, Emine Ipek; Atik, Tahir; Akalin, Taner; Yagci, Ayse
Purpose: To investigate vitamin D receptor polymorphisms in ocular surface squamous cell neoplasm and to evaluate the relationship between the identified polymorphisms and susceptibility to ocular surface squamous cell neoplasm and the clinical course. Materials and Methods: A totala of 70 patients with ocular surface squamous cell neoplasm (study group) and 75 healthy age and gender-matched individuals (control group) were included in the study. Vitamin D receptor FokI and BsmI polymorphisms were examined. The relationships between histopathological diagnosis, recurrence rates, tumor stage, and identified polymorphisms were investigated. Results: Histopathologically, 43 of the cases were squamous cell carcinoma and 27 of the cases were conjunctival intraepithelial neoplasia. The frequency of FokI (FF, Ff, ff) and BsmI (BB, Bb, bb) polymorphism genotype of vitamin D receptor gene were similar in the groups. The frequency of polymorphism (heterozygous or homozygous) for BsmI (Bb and bb) was significantly higher (p = 0.046) in the study group, while no difference was found between the groups in terms of polymorphic carriers (heterozygous or homozygous) for FokI. There was no correlation between tumor stage, recurrence-polymorphism frequency, and patient age-polymorphism frequency. Conclusion: It is known that active vitamin D inhibits the growth of cancer cells by binding to vitamin D receptor with regulation of genes responsible for cell proliferation. The presence of BsmI polymorphism in vitamin D receptor, in particular bb genotype and b allele, appears to be associated with the susceptibility of ocular surface squamous cell neoplasm. BsmI gene polymorphisms of vitamin D receptor might play an effective role in the formation, progression, and in the course of ocular surface squamous cell neoplasm.